Artificial Intelligence in Education and Its Conditional Impact on Critical Thinking: A Systematic Literature Review - Maslan Maslan; Nila Ubaidah (Jurnal Didactical Mathematics, 2026)
The integration of artificial intelligence (AI), particularly generative AI, has transformed contemporary educational practices, raising critical questions about its role in fostering higher-order thinking skills. This study aims to examine how AI influences critical thinking in educational contexts through a systematic literature review of empirical and supporting studies published between 2020 and 2026. Following PRISMA guidelines, 18 studies were selected and analyzed thematically. The findings indicate that AI can enhance critical thinking, problem-solving, and creativity, particularly when embedded in structured learning environments. However, the results also reveal a parallel risk of cognitive dependency, where learners rely on AI-generated outputs without sufficient evaluation. This dual effect highlights a central tension between AI as a cognitive support tool and as a potential substitute for independent reasoning. Furthermore, instructional design emerges as a key mediating factor. Approaches such as scaffolding, problem-based learning, and guided interaction significantly enhance AI's effectiveness in promoting higher-order thinking. The study concludes that AI does not inherently improve or hinder critical thinking; rather, its impact depends on pedagogical integration, learner engagement, and AI literacy. These findings contribute to a more nuanced understanding of AI in education and provide implications for designing learning environments that support meaningful cognitive development.